Hydrodynamic tests on a fixed plate in uniform flow - Klaka, Kim; Penrose, John; Horsley, Richard; Renilson, M. (Elsevier Science Inc., 2005)
The forces and moments acting on a vertical flat plate in open flow running normal to the surface of the plate have been subject to investigation for several decades. However, the forces and moments acting on surface-piercing plates, plates slightly inclined to the vertical and plates extending close to a lower boundary have not received such attention. A series of experiments was conducted as part an investigation into the hydrodynamics of sailing yacht keels, with particular application to the case of a yacht drifting laterally down stream. The results may be of value for a wider range of engineering problems involving the flow of water over surface-piercing plates. It was found that drag force and heel moment varied approximately as flow speed squared for all plates investigated; the influence of plate angle on drag coefficient was small, with no clear trend; the magnitude of the drag coefficients for the surface-piercing plates was greater than for published data on fully submerged plates; and the centre of pressure was at approximately 50% of the span. The data scatter at low Froude numbers restricts the validity of these conclusions to Froude numbers greater than 0.1.